Role of entrepreneurship awareness in engineering education - S, Kishore (Journal of Management and Science, 2021)
Entrepreneurship education teaches engineering students in all disciplines the knowledge, tools, and attitudes that are required to identify opportunities and bring them to life. Despite an increased focused on developing and understanding engineering undergraduates’ entrepreneurial mindsets, best practices related to assessing this mindset remain nascent. While some of these existing studies sought to understand perceptions, attitudes, and beliefs, the existing literature is limited in direct attempts to measure students’ entrepreneurial mindsets or beliefs. In this article, we tried to examine the importance of entrepreneurship efforts in engineering education, national support for entrepreneurship, student and faculty attitudes and engagement. We then offer our perspective on the future landscape for innovation and entrepreneurship in engineering education.